Optimalisasi Kinerja Lembaga Pendidikan Unggul Melalui Implementasi Manajemen Strategik yang Efektif - Kusumaningrum, Hesti; Azahra, Salsabila; Maharani, Sekar Puan; Azzahra, Nurul (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research aims to provide information on how to implement strategic management to improve the performance of superior educational institutions in Indonesia. Strategic management is very important because it provides a framework for directed and sustainable decision-making to improve the quality of education in schools.Method – This research is descriptive research using the literature review method. The data collection technique used is to collect as much theory and information as possible from library materials regarding research topics that are relevant and whose validity can be justified academically.Findings – The research shows that the main urgency for implementing strategic management principles in educational institutions is to help educational institutions formulate more appropriate strategies. Educational institutions in Indonesia have not been able to implement correct strategic management, resulting in the low quality of education in Indonesia. Strategic management is an integration process between formulating or planning, implementing, or applying, and evaluating, which leads to making organizational decisions that have an impact on organizational excellence. If educational institutions can carry out strategic management well, efforts to improve education will be realized, and educational institutions will become increasingly superior. Research Implications – This research implies that school principals who have comprehensive competencies will be better able to implement strategic management in educational institutions. Effective educational leaders in strategic management must be able to manage resources efficiently and have the ability to develop clear and consistent goals and direction, accompanied by good tactical planning.